2013
DOI: 10.1038/nphys2671
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cooper pairing of heavy fermions in CeCoIn5

Abstract: § These authors contributed equally to this research project. The Cooper pairing mechanism of heavy-fermion superconductors 1-4 , while long hypothesized as due to spin fluctuations 5-7 , has not been determined. It is the momentum space (k-space) structure of the superconducting energy gap (k) that encodes specifics of this pairing mechanism. However, because the energy scales are so low, it has not been possible to directly measure (k) for any heavy-fermion superconductor. Bogoliubov quasiparticle interfer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
289
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(312 citation statements)
references
References 34 publications
20
289
2
1
Order By: Relevance
“…However, in CeCoIn 5 this sort of data do not abound. Three previous STS studies claim nodal heavy fermion superconductivity in CeCoIn 5 from either fitting the quasiparticles' excitation spectrum [5], or infering information on the k-space structure of ∆, [6] or detecting close to surface atomic steps a spatial-evolution of low-energy excitations that is typical of nodal superconductivity. [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in CeCoIn 5 this sort of data do not abound. Three previous STS studies claim nodal heavy fermion superconductivity in CeCoIn 5 from either fitting the quasiparticles' excitation spectrum [5], or infering information on the k-space structure of ∆, [6] or detecting close to surface atomic steps a spatial-evolution of low-energy excitations that is typical of nodal superconductivity. [7].…”
Section: Introductionmentioning
confidence: 99%
“…[7]. Nevertheless, performing multi-parameter modeling of the conductance depletion in order to extract spectroscopic information on the superconducting condensate from these experimentally rounded [5] or particle-hole asymmetric [6,7] STS spectra is a strategy that can be further improved in order to produce more confident results. In this work we measured low-temperature STS spectra of CeCoIn 5 with well defined features in the quasiparticle excitation spectra that are the signature of nodal superconductivity, mounted on a featureless background.…”
Section: Introductionmentioning
confidence: 99%
“…9b), Allan et al revealed Bogoliubov QPI patterns related to superconductivity within the energy range of AE1 meV. 81 The closing of the low temperature spectral gap of B550 meV at the bulk T c = 2.1 K, along with images of a square Abrikosov vortex lattice, consistent with that reported by neutron scattering experiments, 84 75 confirmed the observation of superconductivity in CeCoIn 5 . Furthermore, the V-shaped spectra suggested gap nodes, while the QPI patterns imaged (Fig.…”
Section: Quasiparticle Interferencementioning
confidence: 53%
“…81 Above T c , the normal state electronic properties of these materials are dominated by the hybridization of the conduction band (typically a light band of s, p, and/ or d character), with localized f orbitals, resulting in heavy, hybrid bands as sketched in Fig. 9a.…”
Section: Quasiparticle Interferencementioning
confidence: 99%
See 1 more Smart Citation